Digital game education: designing interventions to encourage players’ informed reflections on their digital gaming practices - Marques de Albuquerque, Rafael (2016)
This thesis describes the development, implementation and evaluation of a model of game education, here understood as the process of educating about digital games. The pivotal characteristic of this model is in placing the claimed influences of gaming (e.g. cognitive gains, increase of aggression) at the centre of the content to be learnt. It is based on five principles, namely, that game education can be Informative, Critical, Empowering, Emancipatory, and Dialogic, hence the ICEED Game Education Model. The ICEED model was inspired by both the academic literature and the first study of this thesis, in which 15 University students were interviewed regarding the influences of their gaming practices. Later the model was operationalised in a course named Reflective Gaming Course (RGC), which addresses a series of positive and negative influences of gaming according to the ICEED model. Using a Design Based Research methodological framework, the course was implemented, evaluated and improved as an extracurricular course for adolescents in a secondary school and then in a college, in the second and third study of this thesis. The contributions of the thesis can be divided into four sections. The first is the ICEED Game Education Model, which offers a novel and useful conceptual understanding of what game education can be, hence expanding the possibilities of how game education is conceived. The second section is the Reflective Gaming Course, which is a concrete course plan that can be reproduced or adapted by researchers or practitioners. This course was improved through two implementations, and it was found to be a useful and promising practice. By providing accounts of the course, the process involved, the outcomes achieved, the successes and failures, it is hoped to provide detailed information to inform future projects. The third section is a discussion of the findings with regard to the difficulty of transforming the academic literature on the influences of gaming into useful content for players. This highlights a limitation on the part of research in this area, which often overlooks the potential of its claims to inform players and encourage them to improve their gaming practices. The fourth section concerns knowledge about players’ perspectives about the influences of their gaming practices, complementing other similar studies. In the perspective of participants, some of the topics were perceived as more important (e.g. tangential learning, cognitive gains, excessive gaming) others less so (e.g. connections with school, aggression, stereotypes). Their perspectives also illustrate the recurring absence of opportunities in which players can problematize their perspectives on the influences of gaming.